Flow analysis on boundary layer of porous horizontal circular cylinder filled by viscoelastic-micropolar fluid - Abdul Rahman, Mohd Kasim; Laila Amera, Aziz; Noor Amalina Nisa, Ariffin; Mohamad Hidayad, Ahmad Kamal; Iskandar, Waini; Mohd Zuki, Salleh; Dennis, Ling Chuan Ching (Semarak Ilmu Publishing, 2022)
This study emphasis on the analysis of boundary layer flow of viscoelastic fluid with microrotation moving over a porous horizontal circular cylinder. The model of the problem is based on Navier Stokes equations which involved continuity, momentum and micro inertia equations. The mentioned equations are first undergo Boussinesq and boundary layer approximation before transforming to non-dimensional form which in partial differential equations system. Since the boundary layer equations of viscoelastic fluid are an order higher than Newtonian (viscous) fluid, the adherence boundary conditions are insufficient to govern the solutions entirely. Hence, the augmentation of an extra boundary conditions is necessary to perform the computation. The computation is done by adopting the established procedures called Keller box method. The results are computed for velocity and microrotation distribution as well as skin friction coefficient. It is worth to mentioned at the special case, the present model can be deduced to the established model where the porosity, microinertia and magnetic term excluded. The output computed will be served as a reference to study the complex fluid especially when the fluid exhibit both viscous and elastic characteristics with microrotation effect.